Analysis of Students' Error in Working on Story Problems Based on Newman's Criteria in Class II MIA 3 Man 3 Padang - Surya, Fajar; Edriati, Sofia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The background of this research is that there are still many students who are less interested and motivated in learning mathematics so that many students make mistakes in solving math word problems. The purpose of this research is to identify and identify the types of mistakes made students in working on word problems based on Newman's Error criteria and knowing the causes of students making mistakesIn doing story problems.The research method used is descriptive method with a qualitative approach . The sample of this study were 24 students of class XI MIA 3. The research instrument was tests and interviews. The test results were analyzed based on Newman's criteria, after which students were interviewed based on the types of mistakes made by students.The results of this study indicate that the types of errors made by students based on Newman's criterion analysis consist of 5 errors, namely Reading errors, Comprehension errors, Transformation errors, Process Skill errors and Endcoding errors. The biggest mistake was made at the stage of writing the final answer, namely as much as 46.67%, while the smallest error was made at the stage of understanding the questions, namely as much as 5.33%.